If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + d = -10 + -1d Solving 6 + d = -10 + -1d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add 'd' to each side of the equation. 6 + d + d = -10 + -1d + d Combine like terms: d + d = 2d 6 + 2d = -10 + -1d + d Combine like terms: -1d + d = 0 6 + 2d = -10 + 0 6 + 2d = -10 Add '-6' to each side of the equation. 6 + -6 + 2d = -10 + -6 Combine like terms: 6 + -6 = 0 0 + 2d = -10 + -6 2d = -10 + -6 Combine like terms: -10 + -6 = -16 2d = -16 Divide each side by '2'. d = -8 Simplifying d = -8
| 17-63= | | x^3-8x^2+4x-32=0 | | n/8+5=10 | | -5-2v=-7v | | 3x+3x+3x=198 | | 6(5-4r)=6(4-5r) | | (4/(x+4))-(3/(x-4))=(2x/((x^2)-16)) | | 10+5v=7v-10 | | 6s+5s=-77 | | -g=g+8 | | -5-3y=-18 | | 8h+8=-2+10h | | 7b-5=2b-.5 | | x^3+4x^2-32x=128 | | x/10-2=4 | | -6r=9-7r | | y/17=-5 | | x+5x+(35+x)=385 | | -7=x/4+(-5) | | 2u^2=7u+4 | | 150-1/2= | | 1/6(2x-4)=7 | | 3v^2+9v+4= | | 8x-2/3=4(x+2) | | -2z=z+6 | | 2(1-7b)=-30-6b | | 8-9w=-10w | | -11-2= | | 3v^2+8v=-5 | | 8p=-9+9p | | r/5+6/5=r/7+8/7 | | 9x-(7x-9)=6 |